When sparks fly because of your neighbour’s independent contractor: The stricter-liability test of private nuisance in Singapore – PEX International Pte Ltd v Lim Seng Chye and another and another appeal [2020] 1 SLR 373 - TAY, Samuel Hzi Xun (Institutional Knowledge at Singapore Management University, 2023)
When your land has been damaged by your neighbour’s independent contractor, who should be held responsible—the contractor or your neighbour? Previously, it was considered by some to be difficult to pin liability on one’s neighbour. 1 This position was criticised for being unfair and unjust, especially in situations where one was unable to obtain recourse from the contractor.